Growth options and firm valuation - Holger Kraft; Eduardo S. Schwartz; Farina Weiss (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper studies the relation between firm value and a firm's growth options. We find strong empirical evidence that (average) Tobin's Q increases with firm-level volatility. The significance mainly comes from R&D firms, which have more growth options than non-R&D firms. By decomposing firm-level volatility into its systematic and unsystematic part, we document that only idiosyncratic volatility has a significant effect on valuation. Second, we analyze the relation of stock returns to realized contemporaneous idiosyncratic volatility and R&D expenses. Single sorting on idiosyncratic volatility yields a significant negative relation between portfolio alphas and contemporaneous idiosyncratic volatility for non-R&D portfolios, whereas in a four-factor model the portfolio alphas of R&D portfolios are all positive. Double sorting on idiosyncratic volatility and R&D expenses also reveals these differences between R&D and non-R&D firms. To control for several explanatory variables simultaneously, we also run panel regressions of firm-level alphas which confirm the relative importance of idiosyncratic volatility that is amplified by R&D expenses. Finally, we show that our results are robust to the definition of idiosyncratic volatility. We tease out the ``true'' idiosyncratic volatilities by performing a principal-component analysis on the residuals of Fama-French regressions and find that our main results still hold for this alternative definition of idiosyncratic volatility.
Keywords: G12; 330; Firm valuation; Real options; Volatility; R&D expenses; PCA